2020
DOI: 10.1371/journal.pone.0243966
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between hospitalized patients’ demographics, symptoms, comorbidities, and COVID-19 pandemic in Bahia, Brazil

Abstract: In this paper, we provide a retrospective cohort study with patients that have been hospitalized for general or intensive care unit admission due to COVID-19, between March 3 and July 29, 2020, in the state of Bahia, Brazil. We aim to correlate those patients’ demographics, symptoms and comorbidities, with the risk of mortality from COVID-19, length of hospital stay, and time from diagnosis to definitive outcome. On the basis of a dataset provided by the Health Secretary of the State of Bahia, we selected 3,89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
5
16
1
1
Order By: Relevance
“…In the current study, we found the main predictors of mortality to be male sex, advanced age, cardiovascular disease, diabetes mellitus, chronic respiratory disease, systemic arterial hypertension, obesity and chronic kidney disease. These data corroborate previous studies that indicate the presence of previous comorbidities as an important factor for worsening of the condition [ 27 , 28 , 30 , 32 , 38 , 39 ]. In a study conducted in Pernambuco, Brazil, the presence of cardiovascular diseases, for example, accelerated mortality from COVID-19 by 4 days when compared to individuals without comorbidities [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we found the main predictors of mortality to be male sex, advanced age, cardiovascular disease, diabetes mellitus, chronic respiratory disease, systemic arterial hypertension, obesity and chronic kidney disease. These data corroborate previous studies that indicate the presence of previous comorbidities as an important factor for worsening of the condition [ 27 , 28 , 30 , 32 , 38 , 39 ]. In a study conducted in Pernambuco, Brazil, the presence of cardiovascular diseases, for example, accelerated mortality from COVID-19 by 4 days when compared to individuals without comorbidities [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among survivors, the most frequent symptoms were fever, cough and headache, while respiratory symptoms were more frequent in individuals who died. Other studies have found a significant association between shortness of breath and death risk [ 27 , 32 ] (Macedo, 2020; Soares, 2020). In the respiratory system, angiotensin-converting enzyme 2 expression facilitates the entry of SARS-CoV-2, which mainly infects ciliated cells and type II alveolar cells [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…The pooled overall, prevalence of in-hospital death in Iran country is 12.16% (95% CI: 10.72%-13.61%). This estimation is upper than large cohort study that reported in-hospital death due to COVID-19 in China [8,9] and lower than study reported in in-hospital mortality in USA [11][12][13], Brazil [14], Spain [15][16][17], France [18,19] and Italy [20]. This prevalance is also lower than pooled meta prevalence of in-hospital mortality in patients with COVID-19 in the world [21].…”
Section: Discussionmentioning
confidence: 69%
“…COVID-19 patients had a very high ranging in-hospital death rate of admitted patients. The large cohort study in China ((9.6%)[8], 3.98% [9]), USA (8.2% [10], 18.58% [11], 45.11% [12], 22.77% [13]), Brazil (26.82% [14], Spain (21.3% [15], 20.90%[16], 21.41% [17]), France (16.87% [18], 27.72% [19]), Italy (28% [20]) reported various prevalence of in-hospital death due to COVID-19. Abate et al in a meta analysis study showed that the pooled prevalence of inhospital mortality in patients with coronavirus disease was 15% (95% CI: 13 to 17) [21].…”
Section: Contextmentioning
confidence: 99%
“…This result correlates with previous studies. Cardiovascular disease, cerebrovascular disease, chronic kidney disease and chron-ic lung disease were the most reported comorbidities (3,12,13).…”
Section: Discussionmentioning
confidence: 99%